2012
DOI: 10.1080/09712119.2011.621532
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of equine cervical spine using three-dimensional computed tomographic reconstruction

Abstract: The purpose of this paper was to define the normal three-dimensional computed tomographic reconstruction of the equine cervical spine. Two millimetres thick transverse images of two foals were obtained. Images provided excellent anatomic detail of cervical spine and relevant anatomic structures were identified. Tridimensional reconstruction can be a valuable diagnostic aid for clinical evaluation of several spinal disturbances in foals. In addition, this technique can be used as a tool for teaching anatomy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A prevalence of 24% anomalous C6 was recorded in a recent study with a predilection for Warmblood breeds as these accounted for almost 80% of the affected and included horses . Advanced imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI) are increasingly being applied in the evaluation of horses with suspected cervical spinal disease. However, little published information is currently available on CT and MRI characteristics of equine cervical vertebral morphologic variations.…”
Section: Introductionmentioning
confidence: 99%
“…A prevalence of 24% anomalous C6 was recorded in a recent study with a predilection for Warmblood breeds as these accounted for almost 80% of the affected and included horses . Advanced imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI) are increasingly being applied in the evaluation of horses with suspected cervical spinal disease. However, little published information is currently available on CT and MRI characteristics of equine cervical vertebral morphologic variations.…”
Section: Introductionmentioning
confidence: 99%
“…In large animals, CT has been used sparingly for descriptive anatomic research (Hathcock et al 1995;Morrow et al 2000;De Zani et al 2010;Zafra et al 2012) and several studies have demonstrated the clinical value of CT in diagnosing diseases of the head (Tietje et al 1996;Warmerdam et al 1997). In camelids, CT anatomy of the nasal cavity Wang et al 2008), temporomandibular joint (Arencibia et al 2012), tarsus (Hagag et al 2013) and metatarsus and digits (El-Shafey & Kassab 2013) has been studied, but to the author's knowledge, there is no published material describing the results of CT anatomy of the brain and associated structures in dromedary camel applying bone and soft-tissue CT windows.…”
Section: Introductionmentioning
confidence: 99%
“…The CT scanners used in veterinary medicine are designed to use in human patients; therefore, this type of machines are only suitable for neonatal foals due to size constraints of the CT gantry and scanning table. Due to all these limitations, reports of CT in the horse have been focused on technical procedures (Barbee et al 1987), studies of the head (Vink-Nooteboom et al 1998, Morrow et al 2000, De Zani et al 2010, distal extremities (Peterson and Bowman 1988) and cervical spine (Zafra et al 2012). However, most of these studies were performed on cadaver specimens, but to the author's knowledge similar CT studies in live neonatal foals have not been reported.…”
Section: Introductionmentioning
confidence: 92%